2018
DOI: 10.14238/pi58.2.2018.90-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between oxygen saturation and critical congenital heart disease in newborns

Abstract: Background Critical congenital heart disease (CCHD) is relatively common, with a prevalence of 6-8 in every 1,000 live births. This congenital anomaly is a newborn condition that would be ideally suited for a screening program, if simple and reliable methods were available. Pulse oximetry (PO) has been proposed as a screening method to detect CCHD. Objective To assess for a possible association between decreased oxygen saturation and CCHD in newborns. Methods We conducted a cross-sectional study fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Among children with early detection of CCHD, Tetralogy of Fallot, pulmonary atresia and transposition of great arteries were the most widely found. This study was in line with study in North Sumatra in which the most common CCHD found in early detection were Tetralogy of Fallot and transposition of great arteries [18]. Tetralogy of Fallot is the most common cyanotic heart condition in children, with estimated prevalence 1 in 3,500 to 1 in 4,300 people followed by transposition of great arteries and hypoplastic left heart syndrome [19].…”
Section: Discussionsupporting
confidence: 89%
“…Among children with early detection of CCHD, Tetralogy of Fallot, pulmonary atresia and transposition of great arteries were the most widely found. This study was in line with study in North Sumatra in which the most common CCHD found in early detection were Tetralogy of Fallot and transposition of great arteries [18]. Tetralogy of Fallot is the most common cyanotic heart condition in children, with estimated prevalence 1 in 3,500 to 1 in 4,300 people followed by transposition of great arteries and hypoplastic left heart syndrome [19].…”
Section: Discussionsupporting
confidence: 89%